“Merdeka Belajar Kampus Merdeka” Policies in Indonesia Higher Education Institutions: New Public Policy Reform - Yusriadi, Yusriadi; Farida, Umi; Misnawati, Misnawati; Yusriadi, Yusriadi (JURNAL AL-TANZIM, 2024)
This research analyzes volunteers' perspectives on the effects of the 'Merdeka Belajar Kampus Merdeka' (MBKM) initiative on higher education in Indonesia. The MBKM program signifies a substantial paradigm shift in Indonesia's educational policy, emphasizing a comprehensive, adaptable, and pragmatic approach to learning. The initiative aims to facilitate the transition from theoretical academic knowledge to hands-on competencies required in the workforce, promoting career advancement, experiential learning, and individual maturation. This study employs qualitative analysis of volunteer narratives to examine the perceptions, motivations, and obstacles to implementing the MBKM program. The results underscore the program's efficacy in cultivating social responsibility and community engagement, facilitating diverse and global learning opportunities, and augmenting professional and personal competencies. Nevertheless, obstacles to adjustment, obtaining resources, and managing academic obligations are also apparent. This study emphasizes the necessity for increased resources, support systems, and flexible policies to address the changing demands of education. This study enhances the scholarly conversation surrounding educational reform and volunteerism in Indonesia by providing valuable insights to inform future policy discussions and educational advancements.